The Effect of Dzikr Training To Reducing College Student Anxiety During Thesis Working Period - Ryzky Yandy Yustika; Habib Aditya Kuswantio; Lalu Muhammad Tsaqib Zuljihadi; Rafiq Adli; Hazhira Qudsyi (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This study aims to determine the effect of training dzikir to decrease anxiety in students who are working on their thesis. Respondents in this study were 8 UII students of male gender with age range 23-27 years in the process of thesis. This study used a randomized experimental research design with pretest-posttest two group design. The measuring instrument used in this study is HARS by using repeated measures anova analysis. The results of repeated measures anova analysis show the effectiveness of dhikr training on anxiety decreases by 53,2% with significance equal to 0,04 (p <0,05). So that dzikir training has an influence in decreasing student anxiety level during thesis workmanship.